2023
DOI: 10.3390/ani13162663
|View full text |Cite
|
Sign up to set email alerts
|

Current and Future Advances in the Detection and Surveillance of Biosecurity-Relevant Equine Bacterial Diseases Using Loop-Mediated Isothermal Amplification (LAMP)

Alexandra Knox,
Gemma Zerna,
Travis Beddoe

Abstract: Horses play an important role throughout the world, whether for work, culture, or leisure, providing an ever-growing significant contribution to the economy. The increase in importation and movement of horses, both nationally and internationally, has inevitably allowed for the global equine industry to grow. Subsequently, however, the potential for transmission of fatal equine bacterial diseases has also escalated, and devasting outbreaks continue to occur. To prevent such events, disease surveillance and diag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 188 publications
1
1
0
Order By: Relevance
“…It is worth mentioning that in the comparison against the native reaction, the supplement that least impacted the Tt was pullulan, in agreement with what was previously reported by Gao et al [29], who also demonstrated its compatibility with other isothermal techniques such as CPA and RCA [49]. None of the supplements accelerated NEB for any of the targets, while betaine and DMSO, particularly the latter, did reduce the amplification time of Lava and Syn when targeting ttr, but not the other two targets, which may be related to a decrease in the melting as this target was determined to have a higher %GC; see Table 3 [28,47,[50][51][52].…”
Section: Discussionsupporting
confidence: 89%
“…It is worth mentioning that in the comparison against the native reaction, the supplement that least impacted the Tt was pullulan, in agreement with what was previously reported by Gao et al [29], who also demonstrated its compatibility with other isothermal techniques such as CPA and RCA [49]. None of the supplements accelerated NEB for any of the targets, while betaine and DMSO, particularly the latter, did reduce the amplification time of Lava and Syn when targeting ttr, but not the other two targets, which may be related to a decrease in the melting as this target was determined to have a higher %GC; see Table 3 [28,47,[50][51][52].…”
Section: Discussionsupporting
confidence: 89%
“…In horses, the disease is chronic and can last up to several years. Depending on the localization of the pathological process, the disease is divided into nasal, pulmonary and cutaneous forms (Knox et al 2023). In the acute course, there are septicemia, prolonged and unilateral nasal discharge, swelling of lymphatic vessels, submandibular, inguinal, subcutaneous lymph nodes with the formation of nodules and then ulcers.…”
Section: Introductionmentioning
confidence: 99%